PENGARUH BIAYA PRODUKSI TERHADAP PENDAPATAN USAHA TANI PADI SAWAH - Sari Perwita Rahmanti Ignatia (Fakultas Pertanian, 2023)
Lowland rice as a type of food crop has been widely cultivated by farmers. This is because rice is oneof the staple foods of the community. Lowland rice farming carried out by farmers requires several factorsof production to be able to produce the expected production. The use of production factors certainlyrequires funds that must be spent by farmers for their procurement or purchase. The costs associated withpurchasing factors of production will ultimately affect the amount of income farmers receive. Therefore,farmers need to know the production costs incurred and their effect on income. Farmers are expected tomake several efforts to make efficient use of several factors of production so that they can increase theirincome to improve the welfare of farmers. The effect of production factor costs was analyzed using multiplelinear regression analysis. The hypothesis was tested by comparing the sig values obtained from theanalysis results with a value of 0.0 5. The test results using simultaneous and partial tests stated that landrental costs, seed costs, fertilizer and pesticide costs had a significant effect on farmers' income. Land rentalcosts and seed costs have a positive effect on farmers' income, where an increase/decrease in these costswill increase or decrease farmer income. Fertilizer and pesticide costs have a negative effect on farmers'income, whereby increasing/decreasing these costs will decrease/increase farmers' income. The cost ofrenting a tractor and the cost of labor wages have no effect on farmers' income